Integration of the central part of the territory of Lodz: A configurational analysis - Lamprecht, Mariusz (Przestrzenny wymiar badań dziedzictwa kulturowego: Studia z Geografii Politycznej i Historycznej 2020. T. 9-10, 2021)
The chapter contains the results of the configurational analysis of the inner part of Lodz conducted with the use of space syntax tools. The studies encompassed the area enclosed by the line of the so-called encircling railway, that is the oldest urban structures with their vast surroundings. The research revealed spaces which are crucial (in the configurational context) to the functioning of the city. Depending on the scale of analyses, both a global centre and local structures, the result of the still visible influence of the river network on the structure of the city plan, are distinguishable in Lodz. In light of this information, the city does not appear to have a simple centrifugal urban layout. Instead, the territory of Lodz resembles an archipelago of islands isolated by strips of urban areas with low internal integration.